2020
DOI: 10.1101/2020.12.29.424491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ticks convert pathogenicCoxiellainto endosymbionts

Abstract: Both symbiotic and pathogenic bacteria in the family Coxiellaceae cause morbidity and mortality in humans and animals. For instance, Coxiella-like endosymbionts (CLEs) improve the reproductive success of ticks — a major disease vector, while Coxiella burnetii is the etiological agent of human Q fever and uncharacterized coxiellae cause infections in both animals and humans. To better understand the evolution of pathogenesis and symbiosis in this group of intracellular bacteria, we sequenced the genome of a CLE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 120 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…The main survival strategy of CLE is the vertical transmission via the egg, but also horizontal transfer, possibly via co-feeding, was proven (156,157). Recent results based on genome sequencing have shown that certain CLEs seem to have evolved from an ancestor capable of infection of immune cells (158). Hence, a loss of pathogenic potential was suggested.…”
Section: Unclear Pathogenic Potential Of Coxiella-like Endosymbionts Should Not Be Neglectedmentioning
confidence: 99%
See 1 more Smart Citation
“…The main survival strategy of CLE is the vertical transmission via the egg, but also horizontal transfer, possibly via co-feeding, was proven (156,157). Recent results based on genome sequencing have shown that certain CLEs seem to have evolved from an ancestor capable of infection of immune cells (158). Hence, a loss of pathogenic potential was suggested.…”
Section: Unclear Pathogenic Potential Of Coxiella-like Endosymbionts Should Not Be Neglectedmentioning
confidence: 99%
“…Novel tick-borne pathogens are emerging, and as the evolution of C. burnetii is closely linked to endosymbionts, the possibility of other Coxiella spp. being pathogenic should not be neglected, considering that bird infections or human skin infections were reported (38,49,103,158). Increasing the knowledge on evolutionary processes and the pathogenic potential of CLE could likewise also contribute to a better understanding of the epidemiology of C. burnetii.…”
Section: Unclear Pathogenic Potential Of Coxiella-like Endosymbionts Should Not Be Neglectedmentioning
confidence: 99%
“…in cases (Raulf et al, 2018). Other bacteria of notable prevalence are Coxiella and Francisella, which have been reported to exist symbiotically in ticks such as Rickettsia-like, Coxiella-like, and Francisella-like endosymbiont (Song et al, 2022), and potentially play a crucial role in tick development by supplying B vitamins (Brenner et al, 2021). Networks show the interrelationship between bacteria and Supplementary Tables 6, 7 present the detailed correlation results of groups.…”
Section: Discussionmentioning
confidence: 99%